Variability in date palm (Phoenix dactylifera L.) genotypes in Kachchh, India: a study on morphological and fruiting characteristics (Indian Journal of Arid Horticulture, 2025)
This study investigates the morphological diversity among 38 date palm genotypes grown in Kachchh, India, using Principal      Component Analysis (PCA) and Hierarchical Clustering. A dataset comprising 27 quantitative and qualitative traits were analysed. The correlation analysis revealed significant associations between key traits such as pulp thickness, fruit weight, and pulp-to-stone ratio, which are crucial for fruit quality improvement. PCA identified major traits contributing to morphological variability, with the first three principal components explaining over 52% of total variance. Hierarchical clustering grouped genotypes into four distinct clusters, demonstrating significant genetic diversity. The findings highlight the importance of fruit-related traits in genetic differentiation and provide a framework for breeding superior date palm genotypes.